PENGARUH STRATEGI PEMASARAN TERHADAP KEPUASAN NASABAH PADA PT BANK TABUNGAN NEGARA KCP KOPO - Roisah, Riris; Iskandar, Iis (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2013)
ABSTRACT - Banking competition in the market and business situations are changing very fast. PT. Bank Tabungan Negara as one of the banking institutions in Indonesia, was originally commissioned by the Indonesian government to be the only bank that won the distribution of mortgages, however, with the change in government policy in Indonesia, where the entire mortgage banking channel is allowed, then the State Savings Bank to shift focus business This study aims to determine the marketing strategy, knowing the level of customer satisfaction and to determine the effect of marketing strategy on customer satisfaction at PT. Bank Tabungan Negara KCP Kopo. The research method used is a quantitative method by using statistical analysis. Ans the study is a type of survey, which took samples from the population and use the questionnaire as a measurement tool. The design used in this research is descriptive method of verification for the data analysis used linear regression, coefficient test, determination and t-test. Based on the findings and results of t-test (partial) there is a significant positive effect on customer satisfaction. While the contribution of customer satisfaction marketing strategy shown by koefisisen determination has been described by 0,472, meaning that marketing strategies affect customer satisfaction of 47.2%, while the remaining 52.8% are influenced by variables not examined. And the results of the study showed R = 0.687 R almost close to 1, that mean the variables of marketing strategy to influence customer satisfaction.Keywords: strategy marketing, marketing mix, customer satisfaction.